CRAMP-encoding Lactobacillus plantarum FCQHC24 attenuates experimental colitis in mice. (August 2021) - Pan, Li-Long; Zhang, Ming; Li, Zhengying; Li, Binbin; Pan, Xiaohua; Chen, Xiaopei; Yang, Bo; Zhang, Hao; Chen, Wei; Zhang, Le; Sun, Jia
Abstract: Cathelicidin-related antimicrobial peptide (CRAMP) has been reported to have positive immune-modulatory and anti-inflammatory effects. However, the effect of recombinant CRAMP-encoding Lactobacillus plantarum on experimental colitis is unknown. In this study, 4 strains of CRAMP-encoding L. plantarum FCQHC24 were constructed using genetic engineering. They were administered orally to mice for 4 consecutive days after experimental colitis was induced using 3% dextran sodium sulfate (DSS). Disease severity was determined. The levels of colonic inflammatory cytokines and CRAMP and activation of transcription factor nuclear factor-κB (NF-κB) were analyzed. The 4 engineered CRAMP-encoding L. plantarum strains significantly increased the colonic CRAMP production, especially the strains containing the Usp45 signal peptide, accompanied by reduced colon shortening and body weight (bw) loss. In addition, treatment with the engineered probiotics decreased the levels of colonic pro-inflammatory cytokines (IL-6, IL-1β and TNF-α) and increased the level of colonic anti-inflammatory cytokine IL-10 in DSS-induced experimental colitis. The engineered probiotics suppressed DSS-induced phosphorylation and activation of colonic p38, extracellular signal-regulated kinase 1/2, and NF-κB. Taken together, this study showed that CRAMP-encoding L. plantarum FCQHC2 4 had the therapeutic potential for colitis by modulating colonic CRAMP production. Graphical abstract: Image 1 Highlights: Four types of recombinant CRAMP-encoding L. plantarum strains were constructed. plantarum strains expressing CRAMP with the signal peptide Usp45 produced more CRAMP. CRAMP-encoding L. plantarum strains effectively ameliorated experimental colitis. CRAMP-encoding L. plantarum strains suppressed colonic inflammation. CRAMP-encoding L. plantarum strains attenuated colitis by restoring CRAMP production.